2018
DOI: 10.1186/s13002-018-0238-3
|View full text |Cite
|
Sign up to set email alerts
|

First large-scale ethnobotanical survey in the province of Uíge, northern Angola

Abstract: BackgroundAngola suffered a long-lasting military conflict. Therefore, traditional knowledge of plant usage is still an important part of cultural heritage, especially concerning the still very poor health care system in the country. Our study documents for the first time traditional knowledge of plant use of local Bakongo communities in the northern province of Uíge on a large scale with a focus on medicinal plants and puts data in context to different parameters of age, gender and distance to the provincial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 55 publications
(70 reference statements)
12
67
1
2
Order By: Relevance
“…Grouping the speci c ailments into major ailment categories was made with assistance of a veterinarian at ALIPB, Addis Ababa University, following the approach of Heinrich et al [18]. ICF values were calculated for major disease categories against which at least ve informant use reports were recorded following the approach of Lautenschläger et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Grouping the speci c ailments into major ailment categories was made with assistance of a veterinarian at ALIPB, Addis Ababa University, following the approach of Heinrich et al [18]. ICF values were calculated for major disease categories against which at least ve informant use reports were recorded following the approach of Lautenschläger et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Forests of Uíge Province in northern Angola are full of high value NWFPs, including Dracaena camerooniana Baker, a wild vegetable appreciated by the local population, and an additional source of financial income for subsistence farmers and hunter-gatherers. Furthermore, they constitute a reservoir of firewood for heating [8], handicrafts [8,9], building materials and furniture [8], instruments of music folkloric and religious [8]; edible [8,9], medicinal plants [8,9], rituals [9] and wild animals [8].…”
Section: Introductionmentioning
confidence: 99%
“…These values are low when compared to e.g. the ICF-value (0.71) reported by Ngbolua et al [58] to treat sexual weakness in Kinshasa or by Lautenschläger et al [17] for treatment of intestinal parasitosis (ICF: 0.48), rheumatism (ICF: 0.47) and otitis (ICF: 0.4) in northern Angola in Uíge Province. Low ICF-values could be probably due to the tendency of phytotherapists to keep their knowledge secret from others [59,60].…”
Section: Local Importance Of Plants and Their Consensus Of Use In Dismentioning
confidence: 58%
“…They are to be prioritized for both cultivation and conservation to prevent their disappearance. Heinrich et al [16] and Lautenschläger et al [17] suggested that informant consensus factor (ICF) is a good indicator for selecting plant species best adapted to pharmacological needs and to be subjected to phytochemical analysis.…”
Section: Introductionmentioning
confidence: 99%